2021
DOI: 10.1186/s12951-021-00771-1
|View full text |Cite
|
Sign up to set email alerts
|

Multienzymes activity of metals and metal oxide nanomaterials: applications from biotechnology to medicine and environmental engineering

Abstract: With the rapid advancement and progress of nanotechnology, nanomaterials with enzyme-like catalytic activity have fascinated the remarkable attention of researchers, due to their low cost, high operational stability, adjustable catalytic activity, and ease of recycling and reuse. Nanozymes can catalyze the same reactions as performed by enzymes in nature. In contrast the intrinsic shortcomings of natural enzymes such as high manufacturing cost, low operational stability, production complexity, harsh catalytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(36 citation statements)
references
References 192 publications
(198 reference statements)
0
36
0
Order By: Relevance
“…Nanozymes (NZs)—a class of nanomaterials exhibiting enzyme-like properties and activities—have been tested for a variety of biomedical applications and are promising alternatives to natural enzymes. These abilities are linked to their inherent nanostructures, which mimic natural enzyme active site or charge/electron transfer [ 7 , 8 , 9 ]. The growing interest in NZs is also justified by the fact that these nanomaterials can be easily synthesized and functionalized at a low cost, and their catalytic activities can be tuned without compromising their stability.…”
Section: Introductionmentioning
confidence: 99%
“…Nanozymes (NZs)—a class of nanomaterials exhibiting enzyme-like properties and activities—have been tested for a variety of biomedical applications and are promising alternatives to natural enzymes. These abilities are linked to their inherent nanostructures, which mimic natural enzyme active site or charge/electron transfer [ 7 , 8 , 9 ]. The growing interest in NZs is also justified by the fact that these nanomaterials can be easily synthesized and functionalized at a low cost, and their catalytic activities can be tuned without compromising their stability.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Nanozymes (NZs) as articial enzymes (AEs) are promising alternatives to the natural ones. [1][2][3][4][5] AEs have essential advantages over natural enzymes such as low preparation costs, stability, high surface area, self-assembling capability, size and compositiondependent activities, broad possibility for modication, and biocompatibility. They have wide potential practical applications as catalysts in biosensors, fuel-cell technology, environmental biotechnology, and medicine.…”
Section: Introductionmentioning
confidence: 99%
“…They have wide potential practical applications as catalysts in biosensors, fuel-cell technology, environmental biotechnology, and medicine. [5][6][7][8][9][10][11][12] It has been shown that AEs mimic the activity of peroxidases, 5,[13][14][15] oxidases, 5,16 superoxide dismutases, 5,17 and hydrolases, 5,18 although only limited data were reported regarding reductase mimetics. [19][20][21][22][23][24][25] Natural reductases are the enzymes which belong to the E.C.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, magnetic materials are attracting great attention from researchers due to their promising applications in various fields, such as biotechnology (Alizadeh and Salimi, 2021), catalysis (Liu et al, 2021a), electrochemistry (Wang et al, 2021), and biosensors (Dalkıran et al, 2019). Iron (II, III) oxide (Fe 3 O 4 ) nanocomposites have many applications in the enzymatic immobilization field (Li et al, 2019), as they contain the Fe 3+ (Liu et al, 2016) and Fe 2+ antispinel structures.…”
Section: Introductionmentioning
confidence: 99%